2019
DOI: 10.5650/jos.ess18201
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties, Crystallization Behavior and Oxidative Stabilities of Enzymatic Interesterified Fats of Beef Tallow, Palm Stearin and Camellia Oil Blends

Abstract: Properties, crystallization behavior and oxidative stabilities of enzymatically catalyzed interesterified fats were investigated in this study. Interesterified fats were catalyzed by Lipase Lipozyme RM IM, through reaction from beef tallow (BT), palm stearin (PS) and camellia oil (CO)under the mass ratio of 7.55: 2.45: 4 (BT: CO: PS) using 3.65% (w/w) of Lipozyme RM IM at 72.6℃ for 3.85 h. After reaction, interesterified fats with 36.8℃ sliding melting point (SMP) was obtained. Physicochemical properties (fatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 37 publications
4
9
0
Order By: Relevance
“…MAG, DAG, and TAG contents are expressed in relative percentages of the overall content (Table 3). The results are in accordance with previous studies that observed a decrease in TAG% after interesterification (Kowalski, Tarnowska, & Gruczynska, 2005;Kowalska et al, 2014;Ledóchowska & Wilczyńska, 1998;Pang et al, 2019;Segura & Jachmanián, 2020). Generally, TAG% of enzymatically interesterified lipids were lower than their starting blends.…”
Section: Chemical Propertiessupporting
confidence: 92%
See 3 more Smart Citations
“…MAG, DAG, and TAG contents are expressed in relative percentages of the overall content (Table 3). The results are in accordance with previous studies that observed a decrease in TAG% after interesterification (Kowalski, Tarnowska, & Gruczynska, 2005;Kowalska et al, 2014;Ledóchowska & Wilczyńska, 1998;Pang et al, 2019;Segura & Jachmanián, 2020). Generally, TAG% of enzymatically interesterified lipids were lower than their starting blends.…”
Section: Chemical Propertiessupporting
confidence: 92%
“…The major fatty acids in all interesterified lipids are oleic, palmitic, stearic, and linoleic acids. In general, EI did not cause dramatic changes in the amounts of fatty acids of the structured lipids during the reaction period and similar results were also observed in previous studies (Pang, Ge, Cao, Cheng, & Jiang, 2019;Rønne, Yang, Mu, Jacobsen, & Xu, 2005;Segura & Jachmanián, 2020;Silva et al, 2009;Svensson & Adlercreutz, 2008;). As in the previous researches, enzymatic interesterification of tallow with corn oil did not cause formation of trans-fatty acids (TFA) (Foglia et al, 1993;Forssell et al, 1992).…”
Section: Chemical Propertiessupporting
confidence: 91%
See 2 more Smart Citations
“…Such behavior was expected since, as discussed in 3.2, the concentration of TAG with higher melting points (more saturated) decreased as a result of the process, which was accentuated by the increase in oil content. Similar effects were observed by Pang et al (2019) by interesterifying a blend of BT, palm stearin and Camellia oil, these authors report the decrease and/or disappearance of peaks corresponding to high and low temperatures, increasing and/or appearing peaks at intermediate temperature, they relate this effect to the decrease in homogenous TAG and the increase in heterogeneous TAG due to intersterification. As for the second endothermic peak, peak 3 for the blends, after interesterification, it was split into two peaks (peaks 3 and 4 in the products).…”
Section: Melting Thermogramssupporting
confidence: 73%